One fine day - Hogrogian, Nonny (New York : Trumpet Club, 1971)
After the old woman cuts off his tail when he steals her milk, the fox must go through a long series of transactions before she will sew it back on again.
Reprint: Originally published: New York : Macmillan, c1971.
Keywords: Foxes -- Fiction; Caldecott Medal